Metabolizable energy and amino acid-deficient diets supplemented with β-mannanase in response to growth performance, intestinal health, and immune response in broilers - Myunghwan Yu; Elijah Ogola Oketch; Shan Randima Nawarathne; Nuwan Chamara Chathuranga; Venuste Maniraguha; Bernadette Gerpacio Sta. Cruz; Eunsoo Seo; Jeseok Lee; Haeeun Park; Hyunji Choi; Young-Joo Yi; Kyeong Su Chae; et al. (Poultry Science)
The objective of this study is to investigate the effect of β-mannanase in energy and amino acid-deficient broiler diets on the growth performance, carcass yields, ileal nutrient digestibility, viscosity, intestinal morphology, and blood metabolites of broilers from hatch to day 35. A total of 168 one-day-old Ross 308 broiler chicks were randomly assigned to one of three dietary treatments in a completely randomized design, with each treatment having eight replicates and seven birds per cage. The treatments were as follows: i) positive control diet (PC) containing standard energy and amino acids; ii) negative control (NC) with 150 kcal/kg metabolizable energy (ME) and 4.5 % amino acids reduction compared to PC; iii) NC supplemented with 100 g/ton β-mannanase (NC + β-mannanase). Broilers fed the PC and NC + β-mannanase diets showed improved growth performance, including body weight on day 35 (P < 0.001), average daily gain (Day 1-35; P = 0.001), and feed efficiency (Day 1-35; P < 0.001), alongside lower (P < 0.001) digesta viscosity and enhanced ileal digestibility of dry matter (P < 0.001), crude protein (P < 0.001), and energy (P < 0.001), as well as an improved (P < 0.001) villus height to crypt depth ratio, compared to those on the NC diet. Regarding carcass traits, liver yield was higher (P < 0.001) in broilers on the NC + β-mannanase diet compared to other treatments by day 35. Additionally, the NC + β-mannanase diet lowered (P < 0.001) IL-1β and IFN-γ levels and increased (P < 0.001) IL-10 levels compared to the other groups. In conclusion, β-mannanase supplementation with 100 g/MT β-mannanase in nutrient-deficient diets improved broiler performance by reducing intestinal viscosity and enhancing nutrient utilization efficiency. It also promoted the development of metabolic organs like the liver, as well as immune organs such as the spleen and thymus, while modulating inflammatory and anti-inflammatory cytokine responses.